2018
DOI: 10.1159/000492048
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of Risk Scores to Predict Cerebrovascular Mortality Among Incident Peritoneal Dialysis Patients

Abstract: Background/Aims: Cerebrovascular disease (CeVD) is one of the leading causes of death in patients initialising peritoneal dialysis (PD). Currently there is no risk score to predict the future risk of CeVD on entry into PD. This study aimed to derive and validate a risk prediction model for CeVD mortality in 2 years after the initialisation of PD. Methods: All patients registered with the Henan Peritoneal Dialysis Registry (HPDR) between 2007 and 2014 were included. Multivariable logistic regression modelling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Kelly et al' study found that chronic kidney disease was associated with severe stroke severity, prognosis, and a high burden of asymptomatic cerebrovascular disease and vascular cognitive impairment [ 1 ]. Zhang et al studied the risk prediction model for CeVD mortality by all accessible clinical measures which were screened as potential predictors [ 2 ]. Zeng et al studied the usefulness of predicting CVD in an Inner Mongolian population using the China-PAR equation for 10-year risk [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al' study found that chronic kidney disease was associated with severe stroke severity, prognosis, and a high burden of asymptomatic cerebrovascular disease and vascular cognitive impairment [ 1 ]. Zhang et al studied the risk prediction model for CeVD mortality by all accessible clinical measures which were screened as potential predictors [ 2 ]. Zeng et al studied the usefulness of predicting CVD in an Inner Mongolian population using the China-PAR equation for 10-year risk [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Model discrimination was assessed using the concordance statistic (C-statistic), which was estimated from the adjusted receiveroperating characteristic curves, disregarding the matching. Unconditional logistic regression was performed, with additional adjustment using matching factors [20]. A value of 0.50 represents no discrimination and 1.00 represents perfect discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, having an incident episode of peritonitis within the first 6 months after initializing PD was treated as a binary outcome measure. Candidate prognostic factors that were not statistically significant were excluded from the backward elimination logistic regression model (p > 0.1, based on change in log likelihood) (Zhang et al, 2018b). Two-degree fractional polynomial terms were used to model non-linear associations between outcomes and continuous predictors (Yu et al, 2019).…”
Section: Model Development and Validationmentioning
confidence: 99%
“…We used the concordance statistic (C-statistic) to evaluate model discrimination (Sultan et al, 2016). Model discrimination was internally validated by calculating the bootstrap optimism-corrected c-statistic with 1000 bootstrap replications (Zhang et al, 2018b).…”
Section: Model Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation